In vitro and In vivo characterization of Amyloliquecidin, a novel two-component lantibiotic produced by Bacillus amyloliquefaciens - Van Staden, Anton Du Preez (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.